Transformasi Busana Pengantin Perempuan Lampung dalam Perancangan Adibusana - Pratama, Romi; Santoso, Ratna Endah (Universitas Negeri Surabaya, 2023)
The story behind this work is because there are many people who misinterpret the use of Haute Couture, the term is protected under the Federation de la haute couture et de la mode, even though Indonesian itself has the same term, namely adibusana. Apart from that, the factor behind this design is that there are many generations now who do not know or even leave the tradition of advanced fashion at the level of the shallot bone tribe. The lack of exploration of the wedding dress is the background for the transformation in adibusana design. The design method used is Transforming Tradition by Adhi Nugraha, there are eight important points that can be combined or selected, namely the ATUMICS method. Based on the design process carried out, the results of the collection were obtained with 6 evening dress designs and 4 shoe design to be realized, and 2 bags. This collection required approximately 400 meters of gold thread, 1258 meters of textile pipe, 480 individual chrysolite flowers from textile pipes, thousands of sequins and swarovski, and took approximately 2000 hours to put together the garments.